1991
DOI: 10.1177/112067219100100403
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Haze after Excimer Laser Refractive Surgery: Objective Measurements and Functional Implications

Abstract: Postoperative changes in corneal transparency is a major concern after PRK. Data were obtained from 69 human eyes treated with excimer laser photorefractive keratectomy in order to evaluate a relationship between objective measurements of corneal transparency and visual performance. A CCD-camera device was employed and by using polarizing filters the system could discriminate between reflected and scattered light. We observed two groups of postoperative behaviour in corneal transparency. Each group showed an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(35 citation statements)
references
References 15 publications
0
33
1
1
Order By: Relevance
“…63,64 Human studies have shown that the basal epithelial layer forms hemidesmosomes and new basement membrane within 2 weeks of photoablation. 65 In addition, undulations are most noticeable on the edge of the ablated zone, which would greatly increase the surface area of attachment. Thus, new hemidesmosomes, anchoring fibrils, and epithelial basement membrane are synthesized rapidly and in increasing amounts after PRK, and problems with epithelial instability would therefore not be expected.…”
Section: Anterior Stromal Puncturementioning
confidence: 99%
“…63,64 Human studies have shown that the basal epithelial layer forms hemidesmosomes and new basement membrane within 2 weeks of photoablation. 65 In addition, undulations are most noticeable on the edge of the ablated zone, which would greatly increase the surface area of attachment. Thus, new hemidesmosomes, anchoring fibrils, and epithelial basement membrane are synthesized rapidly and in increasing amounts after PRK, and problems with epithelial instability would therefore not be expected.…”
Section: Anterior Stromal Puncturementioning
confidence: 99%
“…The small amount of scattered light produced by this tissue has in particular been extensively researched in the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. All previous theories explaining corneal transparency [21][22][23][24][25][26][27] have focused on light propagation in the stromal extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…They can be caused by microstructural alterations, the irregular organization of the extracellular matrix, or by cells [22]. Many studies have attempted to relate form, density, and cell size to the structure of the scattered light [1][2][3][4][5][6][7]17,18]. Mourant et al [12,13] suggest that the cell itself is responsible for scattering at a small angle.…”
Section: Introductionmentioning
confidence: 99%
“…Different basic mechanisms underlying the evolution of wound healing which leads to haze formation have been proposed [15][16][17]. Various authors mention the important role of organic free radicals and reactive oxygen species (ROS) generated by UV laser irradiation of the corneal tissue, which could invasively react with the lipid components of cell membranes, nucleic acids and sulfur-containing enzymes and then trigger keratocyte death [18][19][20].…”
Section: Introductionmentioning
confidence: 99%